Nitrogen-rich hierarchically porous carbon as a high-rate anode material with ultra-stable cyclability and high capacity for capacitive sodium-ion batteries. (February 2019) - Hu, Xudong; Sun, Xiaohong; Yoo, Seung Joon; Evanko, Brian; Fan, Fengru; Cai, Shu; Zheng, Chunming; Hu, Wenbin; Stucky, Galen D.
Abstract: Carbon-based anode materials hold a promising future for sodium-ion batteries (SIBs) due to their natural abundance and low cost of development. In spite of carbon's important role in the commercialization of lithium-ion batteries (LIBs), further exploration is necessary in order to find high-performance, high-rate carbon anode materials for SIBs. A honeycomb-like, nitrogen-rich (17.72 at%), hierarchically porous, and highly disordered carbonaceous material (N-HC) with an expanded interlayer distance (0.44 nm in average) is synthesized by spray drying and subsequent pyrolysis under flowing NH3 . The hierarchically porous structure and rich nitrogen doping result in a large specific surface area (722 m 2 g −1 ), more defects and active sites, and greater functional interface accessibility for the active porous carbonaceous material and electrolyte. When N-HC is used as the anode material for SIBs, the batteries display favorable discharge capacities (255.9 mA h g −1 in the 3000th cycle at 500 mA g −1 ) and good capacitive-energy-storage behavior (67% at a scan rate of 0.5 mV s −1 ) with excellent high-rate performance and ultra-stable cyclability over 10, 000 cycles at 5000 mA g −1 . Our results show that the combination of the hierarchically porous structure and nitrogen doping leads to improved energy storage by increasing the capacitive energy storage, which enhances the high-rate performance of N-HC. To further enhance the performance of the material, an electrical pretreatment is employed to increase the initial Coulombic efficiency of N-HC to 79.5%, a record high for an SIB cell. A full cell with an N-HC anode and a Na3 V2 (PO4 )3 /C cathode shows a high capacity with a favorable cyclability (238.7 mA h g −1 after 100 cycles at 100 mA g −1 and a capacity retention of 95.3% compared to the second cycle). Graphical abstract: Highlights: Nitrogen-rich hierarchically porous carbon with expanded interlayer is synthesized. High-rate capability with ultra-stable cyclability is achieved at 5 A g −1 . Sodium storage is dominated by capacitive energy storage for high-rate capability. Enhancing capacitive energy storage in carbon is systematically studied in depth.